Customer Satisfaction Index On The Electrical Buses (Electrical Vehicle) In Malaysia: Case Study On The Affordability, Safety and Accessibility - Mohamed Sharol Zizi Md. Shabarien, Mohamed Sharol Zizi Md. Shabarien; Mohd Fahmy-Abdullah, Mohd Fahmy-Abdullah; Suliadi Firdaus Sufahani, Suliadi Firdaus Sufahani; Wan Ahmad, Wan Noor Afifah (2023)
Public transportation is an important facility that developing countries must incorporate. At the same time, public transport is often related to gas emissions and pollution. All parties, including Malaysia, play an active role in reducing energy consumption and carbon dioxide emission. One of the national efforts is to equip the urban transit system with sustainable development vehicles such as electric buses. In increasing public transportation usage, electric bus services should be designed to accommodate the service required by customers. This research aims to identify the service quality based on a few elements needed to develop customer satisfaction among electrical bus users in Bandar Pengerang by adopting the Customer Satisfaction Index analysis. The main elements to measure are affordability, safety, comfort, and accessibility of the customers to the electric buses. In addition, this research also provides a descriptive analysis of the service quality elements to improve customer satisfaction in public transportation operations